The devil knows more because it is fantastic than because it is old: The tradition of the demonic covenant in Gorriti, Garmendia and Arreola - Amatto Cuña, Alejandra Giovanna (2022)
This article is dedicated to exploring the tradition of the demonic pact and its cultural scope, from a literary perspective, in three stories that are references to the fantastic narrative on the subject and whose authors are essential for the construction of the genre in Latin America: Juana Manuela Gorriti, Julio Garmendia and Juan José Arreola. The first two stories, “Una visita infernal” and “El alma”, will be analyzed from a perspective that places them as “background”, that is, two first experiences that approach the subject in a bold and provocative way, displaying textual aesthetics. anticipated to the nineteenth-century context in the case of Gorriti and avant-garde in the case of Garmendia, with substantial elements that will be seen in a more articulated and profound way in the development of the last story: “A pact with the devil”, by the Mexican Juan José Arreola. From a comparative perspective, some outstanding elements will be seen in the transformation of both the handling of the subject and its textual strategies.